2011
DOI: 10.4314/jasem.v15i1.65673
|View full text |Cite
|
Sign up to set email alerts
|

Ecological assessment of a coastal shallow lagoon in Lagos, Nigeria: A bio-indicator approach

Abstract: ABSTRACT:Benthic macro-invertebrates of the Northern axis of metropolitan segment of Lagos Lagoon sediments, Nigeria were investigated for six months (April -September, 2010). The study was aimed at using benthic macro-invertebrates to assess the water quality of this part of the Lagoon. A total of ten taxa belonging to three major animal phyla from a total of 2,672 individuals were encountered. The dominant taxa throughout the study and stations were Pachymelania aurita, Aloidis trigona, and Neritina glabrata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…The island is a coastal terrain and is surrounded by rural and urban development, only accessible by boats. Reports have shown that there has been an increase in the discharge of domestic, municipal and industrial effluents, as well as contaminants associated with sand mining, oil and gas industrial tank farms and shipping activities, threatening the ecosystem services that Lagos Lagoon provides (Balogun, Ladigbolu, & Ariyo, 2011;Amaeze, Egonmwan, Jolaoso, & Otitoloju, 2012;Alani, Drouillard, Olayinka, & Alo, 2012;Sogbanmu et al, 2016) Ajagbe et al (2012 recommended the need for more studies to establish the state of pollution in the Lagos Lagoon and the levels of pollutants that are detrimental to the ecosystem health and to humans due to the consumption of contaminated fish. Department of Petroleum Resources (DPR) has described Lagos Lagoon as an important economic and sensitive estuarine ecosystem.…”
Section: Study Areamentioning
confidence: 99%
“…The island is a coastal terrain and is surrounded by rural and urban development, only accessible by boats. Reports have shown that there has been an increase in the discharge of domestic, municipal and industrial effluents, as well as contaminants associated with sand mining, oil and gas industrial tank farms and shipping activities, threatening the ecosystem services that Lagos Lagoon provides (Balogun, Ladigbolu, & Ariyo, 2011;Amaeze, Egonmwan, Jolaoso, & Otitoloju, 2012;Alani, Drouillard, Olayinka, & Alo, 2012;Sogbanmu et al, 2016) Ajagbe et al (2012 recommended the need for more studies to establish the state of pollution in the Lagos Lagoon and the levels of pollutants that are detrimental to the ecosystem health and to humans due to the consumption of contaminated fish. Department of Petroleum Resources (DPR) has described Lagos Lagoon as an important economic and sensitive estuarine ecosystem.…”
Section: Study Areamentioning
confidence: 99%
“…Even though lagoons are shallow water bodies, the Lagos Lagoon that is the lagoon for consideration in this chapter (our research) has some parts around the inlets that are deep (12-17 m) as a result of continuous dredging either for the purpose of sand mining and reclamation or for channel navigation. Likewise, it is considered too brackish during the dry season and a fresh water lagoon during the raining season [50,51].…”
Section: Lagoon Stratificationmentioning
confidence: 99%
“…The low abundance of majority of the sea stars, composition and diversity recorded in this study may be attributed to stress imposed by indiscriminate anthropogenic activities (Ajao et al, 1996) such as industrial effluent discharge, oil wastes, domestic waste, and sewage discharges among others as human related activities are capable and presently destroying the sensitive coastal environment (Balogun et al, 2011).…”
Section: Species Compositionmentioning
confidence: 99%